The social space of poverty as an object of sociological analysis - Klyuev, Alexey; Šuvaković, Uroš V.; Bagirova, Anna; Kozitsina, Tatiana (Sociološki pregled, 2026)
The article explores the conceptualization of the “social space of poverty” and its relevance for contemporary sociological analysis of poverty. A scoping review of international (Web of Science) and national (RSCI, SCIndeks) publications was conducted to identify prevailing theoretical and methodological approaches — social exclusion, capability approach, welfare regimes, institutional theory, co-production, and social space. Bibliometric analysis reveals that, despite its relatively limited quantitative presence, the social space concept demonstrates high disciplinary relevance: its citation impact and Hirsch index are significantly higher in sociology journals compared to the broader interdisciplinary field. Using the bibliometric tool VOSviewer, the study maps the structural clusters and semantic dynamics of poverty research, showing a shift from macro-structural categories (exclusion, inequality, paternalism) toward agency-oriented approaches that emphasize subjective experience and strategies for overcoming poverty. The paper argues for the introduction of the analytical category “social space of poverty”, integrating structural, resource-based, and agentic dimensions and reflecting the transition from static representations of poverty toward a procedural perspective focused on individual and collective pathways of overcoming deprivation.